Liquid metals: early contributions and some recent developments - Regnaut, C.; Amokrane, S. (Condensed Matter Physics, 2017)
We illustrate in this contribution the progress in the theoretical study of liquid metals made in the last decades,
starting from the example of liquid gallium and the early work in Jean-Pierre Badiali’s group. This was based on
the combination of the perturbation theory with pseudo-potentials for the electrons and the liquid state theory
for the ions. More recent developments combining ab initio and classical molecular dynamics simulations are
finally illustrated on the example of glass forming alloys. В цiй статтi ми обговорюємо розвиток теоретичних дослiджень рiдких металiв, виконаних за останнi десятилiття, починаючи з прикладу рiдкого галiю i раннiх робiт в групi Жана-П’єра Бадiалi. Вони грунтуються
на поєднаннi теорiї збурень з псевдопотенцiалами для електронiв i теорiї рiдкого стану для iонiв. Наприкiнцi, на прикладi склоутворюючих розплавiв, проiлюстровано пiзнiшi дослiдження, якi поєднують метод
ab initio та класичний метод молекулярної динамiки.